Self-Regulated Learning and Peer Interaction as Drivers of Creativity: A Moderated Mediation Perspective - Nurfaizal, Yusmedi; Agapito Barros (Universitas Brawijaya, Indonesia, 2025)
The rapid digital transformation of higher education requires students to possess not only cognitive and technical skills but also self-regulation and creativity in online learning contexts. These demands highlight the importance of understanding psychological and social processes that influence creative behavior in university students. This study aims to examine the effect of self-regulated learning and peer interaction on creative behavior, with academic self-efficacy as a mediating variable and online learning environment as a moderating variable. This study used a quantitative approach with a cross-sectional survey design. The population included undergraduate students majoring in Computer Science from three universities in Banyumas Regency, Indonesia. A proportional stratified random sampling technique was applied, resulting in 300 valid respondents. Data collection was carried out using a structured questionnaire with Likert-type scales, and data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 application. The findings indicate that both self-regulated learning and peer interaction have a positive influence on students’ creative behavior. Academic self-efficacy was found to partially mediate these relationships, while perceptions of the quality of the online learning environment moderated the impact of both self-regulated learning and academic self-efficacy on creative behavior. These results suggest that student creativity in higher education can be enhanced through a combination of self-directed learning strategies, social interaction, motivational reinforcement, and a well-structured digital learning environment.